Taking preventative health messages into the wider caring professions: the views of housing staff and tenants. (10th October 2018) - Blank, Lindsay; Holding, Eleanor; Crowder, Mary; Butterworth, Sally; Ferrari, Ed; Goyder, Elizabeth
ABSTRACT: Background: In order to harness the potential impact of the wider public health workforce, innovative services are providing opportunities for social housing staff to extend their public health role. This study explored the views of housing professionals and social housing residents on the delivery of preventative health messages by housing staff in the context of the evaluation of the roll-out of a new service. Methods: We conducted semi structured interviews with 21 neighbourhood housing officers, 4 managers and 30 social housing tenants to understand their views on the widening role and the potential impact on the preventative healthcare messages being delivered. Results: Neighbourhood officers were willing to discuss existing health conditions with tenants; but they often did not feel comfortable discussing their lifestyle choices. Most tenants also reported that they would feel discussions around lifestyle behaviours to be intrusive and outside the remit of housing staff. Conclusions: Resistance to discussions of lifestyle topics during home visits was found among both housing staff and tenants. Appropriate staff training and the development of strong and trusting relationships between officers and tenants is needed, if similar programmes to extend the role of housing staff are to succeed in terms of health impact.